Evaluation of Suitability Area for Development of Seaweed Culture (Kappaphycus alvarezii) at Lontar village, District Tirtayasa, Serang - Yunizar Bagus Dewanto; Saifullah Saifullah; Dodi Hermawan (JURNAL PERIKANAN DAN KELAUTAN, 2015)
Seaweed has been cultivated with the purpose to meet a demand of market which incrense immediately. One of factors that can determine the success of seaweed culture is the right location to meet requirement for seaweed cultivation. The purpose of this study to analyze physical and chemical parameters in the Lontar village. Determination of station with randomized method that represent the location that includes 5 stations with repetition three times. Measurement of physical and chemical parameters that the brightness of the water, wave height, current velocity, depth, temperature, salinity, pH conducted at research sites. While for nitrate, phosphate and TSS parameter were measured in the analysis laboratory of department of water resources and settlements (DSAP provinsi Banten). Results of testing the physical and chemical parameters in the waters of Lontar village at District Tirtayasa, Serang, in November-December 2014 can be stated suitable to be used as a location for seaweed cultivation Kappaphycus alvarezii. While the test results showed that the suitability of the location of all stations which observed were stated kind and proper to be used as a location for seaweed cultivation Kappaphypus alvarezzi.